Cultural Literacy Indicators for Elementary Schools: A 4D Model Development - Erlisnawati Erlisnawati; Hendri Marhadi (Jurnal Prima Edukasia, 2025)
This study aims to develop and validate cultural literacy indicators for elementary school students, focusing on their competence to understand, analyze, and apply cultural values in daily life. Using a Research and Development (R&D) approach with the 4D model; Define, Design, Develop, and Disseminate. The development process involved validation by two expert judgments and was contextualized with students at Teratak Air Hitam 007 Elementary School, Kuantan Singingi Regency. The study produced four domains of cultural literacy, namely: (1) cultural diversity, (2) diversity of cultural values, (3) participation in culture, and (4) cultural awareness, each represented by specific indicators. These indicators are distinguished by their adaptability to local cultural contexts and systematic integration into elementary education, making them more contextually relevant. The experts confirmed that the indicators are valid, reliable, and academically relevant as instruments for assessing students’ cultural literacy, providing practical guidance for educators and researchers to evaluate and strengthen cultural literacy in elementary schools and contribute to the advancement of culturally responsive education.